(untitled) (Global Journal of Management and Business Research, 2020)
The objective of this paper is to assess the effect of institutional governance on the relationship between the reaction of monetary authorities when the economy faces a shock and economic growth in the countries of the Sub- Saharan Africa. To achieve this, econometric estimates were made using the Generalized Moment Method (MMG) in a dynamic panel of 36 countries in the zone over the period from 2000 to 2018. The results obtained show that monetary policy as a policy macroeconomic is not a tool for stabilizing economic activity. This low level of democracy in these countries therefore has the effect of amplifying this pro-cyclical behavior of monetary policy. Governments genuinely infer in the implementation of monetary policies, thereby causing this pro-cyclical bias.